Structural and dynamic characterization of the Golgi Reassembly and Stacking Protein (GRASP) in solution - Mendes, Luis Felipe Santos (2018)
The Golgi complex is an organelle responsible for receiving synthesized cargo from the endoplasmic reticulum for subsequent post-translations modifications, sorting and secretion. A family of proteins named Golgi Reassembly and Stacking Proteins (GRASP) is essential for the correct assembly and laterally tethering of the Golgi cisternae, a necessary structuration to keep this organelle working correctly. The GRASP structure is mainly composed of two regions: an N-terminal formed by two PDZ domains connected by a short loop (GRASP domain) and a non-conserved C-terminal region, rich in serine and proline residues. Although there are now a few crystal structures solved for the N-terminal domain, it is surprising to notice that no information is currently available regarding a full-length protein or even about dynamic and structural differences between the two PDZs in solution, which is the main functional region of this protein. Using a full-length GRASP model, we were capable of detecting the coexistence of regular secondary structures and large amounts of disordered regions. The overall structure is less compact than a regular globular protein and the high structural flexibility makes its hydrophobic core more accessible to solvent. GRASP coexist in a dynamic conformational ensemble of a µs-ms timescale. Our results indicate an unusual behavior of GRASP in solution, closely resembling a class of collapsed intrinsically disordered proteins called molten globule. We report here also the disorder-to-order transition propensities for a native molten globule-like protein in the presence of different mimetics of cell conditions. Changes in the dielectric constant (such as those experienced close to the membrane surface) seem to be the major factor capable of inducing several disorder-to-order transitions in GRASP, which seems to show very distinct behavior when in conditions that mimic the vicinity of the membrane surface as compared to those found when free in solution. Other folding factors such as molecular crowding, counter ions, pH and phosphorylation exhibit lower or no effect on GRASP secondary structure and/or stability. This is the first study focusing on understanding the disorder-to-order transitions of a molten globule structure without the need for any mild denaturing condition. Regarding the PDZs that form the GRASP domain, we observed that GRASPs are formed by a more unstable and flexible PDZ1 and much more stable and structurally well-behaved PDZ2. More than that, many of the unstable regions found in PDZ1 are in the predicted binding pocket, suggesting a structural promiscuity inside this domain that correlates with the functional promiscuity of interacting with multiple protein partners. This thesis presents the first structural characterization of a full-length GRASP, the first model of how GRASPs (or any molten globule-like protein) can be modulated by the cell during different cell functionalities and the first work in the community proving that the established idea that both PDZs are structurally equivalent is not completely right